Plasticity of Select Primary Afferent Projections to the Dorsal Horn after a Lumbosacral Ventral Root Avulsion Injury and Root Replantation in Rats - Bigbee, Allison J.; Akhavan, Mahnaz; Havton, Leif A. (Frontiers in Neurology, 2017)
Injuries to the conus medullaris and cauda equina portions of the spinal cord result in neurological impairments, including paralysis, autonomic dysfunction, and pain. In experimental studies, earlier investigations have shown that a lumbosacral ventral root avulsion (VRA) injury results in allodynia, which may be ameliorated by surgical replantation of the avulsed ventral roots. Here, we investigated the long-term effects of an L6+S1 VRA injury on the plasticity of three populations of afferent projections to the dorsal horn in rats. At 8 weeks after a unilateral L6+S1 VRA injury, quantitative morphological studies of the adjacent L5 dorsal horn showed reduced immunoreactivity for the vesicular glutamate transporter, VGLUT1 and isolectin B4 binding, whereas immunoreactivity for calcitonin gene-related peptide (CGRP) was unchanged. The immunoreactivity for VGLUT1 and CGRP as well as isolectin B4 binding were at control levels in the L5 dorsal horn at 8 weeks following an acute surgical replantation of the avulsed L6+S1 ventral roots. Quantitative morphological studies of the L5 dorsal root ganglia (DRGs) showed unchanged neuronal numbers for both the VRA and replanted series compared to shams. The portions of L5 DRG neurons expressing immunoreactivity for VGLUT1 and CGRP, and isolectin IB4 binding were also the same between the VRA, replanted, and sham operated groups. We conclude that the L5 dorsal horn shows selective plasticity for VGLUT1 and isolectin B4 primary afferent projections after an L6+S1 VRA injury and surgical repair.